A RETROSPECTIVE CROSS-SECTIONAL OBSERVATIONAL STUDY INVESTIGATING THE PREVALENT AETIOLOGIES AND CO-MORBIDITIES IN PATIENTS PRESENTING WITH VERTEBRA PLANA IN A SINGLE CENTER SPINE UNIT IN KWAZULU-NATAL, SOUTH AFRICA. - Mgoduka, Zovuyo; Malleck, Gunseli; Puddu, Alberto; Mabusha, Sepeleng (Student’s Journal of Health Research Africa, 2024)
Background Vertebral plana (VP), characterized by the flattening of vertebrae, presents a diagnostic challenge due to its myriad causes. This study investigated the common histological diagnoses of VP within the unique healthcare context of the King Dinuzulu Hospital Complex (KDHC) Spine Unit in Durban, South Africa, to identify the most common aetiologies in this setting to guide management and prognosis. Methods A retrospective observational study was conducted, involving a review of medical records from January 2015 to December 2020. A cohort of 32 patients with VP was analysed for demographics, clinical presentation, imaging findings, and histological diagnoses. The primary objective was to identify prevalent histological causes, enhancing diagnostic precision. Results The mean age of participants was 51.1 years, with a slight female predominance. Most patients had low albumin levels and were classified as having complete neurological injury or normal neurological function. HIV status revealed a 34.4% prevalence, influencing histological diversity, while 31.25% had comorbidities, primarily hypertension. The lumbar spine, particularly L2, was frequently affected, correlating with neurologic fallout. Histological analysis revealed a surprising diversity, with multiple myeloma (26.09%) and plasmacytoma (21.74%) emerging as leading diagnoses, challenging prior assumptions. The study found no significant difference in comorbidity prevalence between genders, but a statistically significant discrepancy in the prevalence of diabetes and reduced vertebral density (RVD) between females and males. Conclusion This study challenges prevailing assumptions about the aetiology of VP, emphasizing the necessity for a nuanced approach to diagnostic investigations. The unexpected prevalence of multiple myeloma and plasmacytoma suggests a shift in VP aetiology, prompting a re-evaluation of clinical practices. Recommendation The study paves the way for further investigation into the pathophysiology and clinical features of vertebra plana. Future research should include multi-institutional diagnosis comparisons and evaluate outcomes based on early versus late or inappropriate management.